Moluskum kontagiosum dengan human immunodeficiency virus stadium IV yang diterapi dengan KOH 20% - Michael Hostiadi; I Gusti Ayu Agung Elis Indira; Ni Made Dwi Puspawati; Ketut Wida Komalasari (DiscoverSys Inc., 2022)
Background: The prevalence of molluscum contagiosum (MC) was found to increase in the HIV population with a prevalence of 5-18%. Persistent molluscum lesions gradually increase in size. Some develop into giant, tumor-like, nodular lesions that can exceed 1 cm in diameter and cause esthetic defects in HIV-positive patients. Conventional treatment is usually not effective enough and requires additional therapy in immunocompromised cases. Case: A 31-year-old woman with stage IV HIV had the main complaint of a skin-colored rash near the genital area. Venereological examination found multiple papules with smooth, shiny surfaces with central umbilication discrete configuration and localized distribution. The molluscum body comes out after being squeezed. The treatment given is 20% potassium hydroxide spots on MC lesions every 24 hours topically. Two weeks after therapy was given, no new lesions were found without any side effects. Conclusion: Administration of 20% potassium hydroxide can be considered an MC treatment option in HIV patient with minimal side effects and is easy to use. Latar Belakang: Prevalensi moluskum kontagiosum (MK) didapatkan meningkat pada populasi human immunodeficiency virus (HIV) dengan prevalensi 5-18%. Lesi moluskum persisten yang secara bertahap bertambah besar, beberapa berkembang menjadi raksasa, seperti tumor, lesi nodular yang dapat melebihi diameter 1cm, dan dapat menyebabkan kecacatan secara estetik sering ditemui pada pasien dengan HIV positif. Pengobatan konvensional biasanya tidak cukup ampuh dan membutuhkan tambahan terapi lainnya pada kasus imunokompromais. Kasus: Seorang perempuan usia 31 tahun, HIV positif stadium IV dengan keluhan utama berupa bintil-bintil bewarna serupa kulit di dekat area genital, bila ditekan keluar bintik putih seperti nasi. Pemeriksaan venereologis ditemukan papul multipel permukaan licin berkilat dengan umbilikasi sentral konfigurasi diskret dengan distribusi lokalisata. Penatalaksanaan yang diberikan adalah tutul kalium hidroksida (KOH) 20% pada lesi MK setiap 24 jam topikal. Dua minggu setelah terapi diberikan tidak ditemukan adanya lesi baru dan tanpa adanya efek samping. Simpulan: Pemberian KOH 20% dapat dipertimbangkan sebagai pilihan terapi MK pada HIV dengan efek sampung minimal dan mudah digunakan.